Pelatihan Dasar Penulisan Karya Tulis Ilmiah untuk Meningkatkan Kemampuan Akademik Siswa SMA Unggulan Al Azhar Medan - Nurhayati Nurhayati; Khoiruddin Matondang; Risna Mira Bella Saragih (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2026)
This community service activity aims to improve students' academic abilities through basic training in writing scientific papers at Al Azhar Superior High School Medan. The problems found show that most students still have difficulties in understanding the structure of scientific papers, the use of academic language, citation techniques, and the appropriate use of scientific references. Therefore, training activities are needed that are able to help students understand the basics of scientific writing systematically. Service activities are carried out in the form of training, practice, and assistance in writing simple scientific papers. The participants of the activity consisted of 30 students in grade XI of Al Azhar Superior High School Medan. The method of implementing activities includes lectures, discussions, demonstrations, direct practice, and participant assistance. The training material includes the definition of scientific writing, the structure of scientific papers, title and introduction writing techniques, the use of references, simple citation techniques, as well as academic ethics and plagiarism. Evaluation of activities is carried out through observation, results of participants' practices, and participant response questionnaires. Training has a positive impact on improving students' academic understanding and abilities. Most of the participants were able to compile simple scientific paper titles, understand the basic structure of scientific papers, and begin to understand the use of simple citation references and techniques. In addition, participants showed enthusiasm and active participation during the activity. This service activity also increases students' motivation and confidence in compiling simple scientific papers. Thus, basic training in writing scientific papers can be one of the effective efforts in improving academic literacy and scientific writing skills of students in the school environment.